SIZE AND SHAPE ANALYSIS OF FEMALE NOSE IN MALAY ETHNIC: ANALISIS UKURAN DAN BENTUK HIDUNG WANITA SUKU MELAYU - Zainul Rajion; Ali Al-khatib; Ahmad Yusdirman Yusof; Rozita Hassan; Sam’an Masudi (Dentika: Dental Journal, 2009)
Several non invasive methods have the results showed that been applied to quantify facial soft tissue morphology. Digitalphotography is one of the methods that has been used in the assessment of facial profile in different population. This studyaims to determine nasal soft tissue differences among Malays in Peninsular Malaysia by applying geometricmorphometric method with digital photograph. A cross sectional study was carried out on 20 participants from Bugis andJava females with aged range from 20-40 years. The photographs were captured using digital SLR camera (Nikon D80)and analyzed using finite element analysis in MorphoStudioTM software. Seven soft tissue landmarks were digitized oneach frontal photograph and six on the lateral one. The study error for both samples was within acceptable limits as therewere no statistical differences (p>0.05) in duplicated digitization. The results showed that the comparison of size revealedthat Bugis females were smaller in upper and lower nasal region about 17- 33%. Bugis females shape showed differencesin upper and lower nasal area by 20%. In lateral profile there was a decreased size in lower nasal area in Bugis females by17- 33% and the difference in shape by 20%. The nasal region was significantly smaller in size and more different inshape for Bugis females than Javanese females. Computer aided photogrammetric analysis has the ability to depict andquantify local shape and size changes of nasal soft tissue differences between Java Malay and Bugis female groups.